Contract Farming in Developing Countries: The promise and its perils - Narayanan, Sudha (Palgrave Macmillan Cham, 2025)
Contract farming is an institutional arrangement between farmers and businesses to produce and transact agricultural commodities at predetermined prices and conditions, and it has recently received a heightened amount of attention despite being a relatively old phenomenon. A new wave of agricultural industrialization and the emergence of large-scale food retailing in developing countries may be precipitating the unprecedented shift in favor of contract farming.